Spontaneous Ovarian Pregnancy and Over Protective Management: A Case Report - Soydinç, Hatice Ender; Evsen, Mehmet Sıddık; Sak, Muhammet Erdal; Çaça, Fatmanur; Özler, Ali (Gynecology Obstetrics & Reproductive Medicine, 2013)
We aimed to present a case of primary ovarian pregnancy in a 31-year-old patient who presented to the emergency room with symptoms and signs of acute abdomen and positive beta HCG test. A gestation sac of 6 weeks was detected in the right ovary by transvaginal sonography. Emergency laparotomy and extirpation of the ectopic tissue was performed.